A new methodology to track the dynamics of structural transformation applied to the case of a developing country - Zakaria Elouaourti; Aomar Ibourk (Journal of Open Innovation: Technology, Market and Complexity)
This paper introduces a novel empirical approach, combining sigma convergence and sigma counterfactual statistics, to examine the dynamics of structural transformation in Morocco from 1990 to 2018. The findings reveal that Morocco experienced structural transformation driven by labor productivity reallocation across sectors during specific sub-periods (1991–1993, 1996–1997, and 1998–2003). However, this process came to an abrupt halt after 2004. Sectoral analysis highlights that the reallocation of labor from the primary and secondary sectors to the tertiary sector contributed to the observed changes, particularly during the early 2000s. By proposing this innovative methodology, the study makes a significant contribution to the literature on structural transformation, offering a replicable framework to analyze similar dynamics in diverse contexts and addressing a critical methodological gap.